Perceived risks, reasons for use, and barriers to cessation among youth who use multiple tobacco products - Sierra L. Patterson; Isabelle Duguid; Sonia A. Clark; Seth M. Noar; Allison J. Lazard; James F. Thrasher; Adam O. Goldstein; Sarah D. Kowitt (PLoS ONE, 2025)
Background Many interventions aim to reduce youth tobacco use, but few have focused on youth who use multiple tobacco products (MTPs). This qualitative study sought to understand how youth who use MTPs view tobacco product risks, describe reasons for MTP use, and perceive barriers and facilitators to cessation. Methods We conducted seven virtual focus groups with 30 US youth ages 14–20 years who reported using e-cigarettes and smoking a combustible tobacco product in the past 30 days. We used a semi-structured focus group guide to ask youth about perceived health risks of tobacco products, reasons for MTP use, and thoughts about quitting. We conducted a thematic analysis of transcripts. Results The mean age of participants was 18.7 years; 47% identified as white. Most participants were female (63%) and lesbian, gay, or bisexual (63%). Three central themes emerged: 1) uncertainty or misperceptions about e-cigarettes were common, including what ingredients they contain, whether they are tobacco products, and their harm relative to cigarettes; 2) convenience and social factors were mentioned as reasons for using MTPs, rather than using e-cigarettes to quit cigarettes; 3) barriers to cessation included nicotine dependence (especially to e-cigarettes) and environmental factors, while cessation resources were rarely mentioned. Conclusions These findings suggest that educational interventions to reduce youth MTP use could focus on correcting misperceptions about e-cigarettes and communicating the harms of combustible tobacco use. Furthermore, behavioral interventions could capitalize on peer and social support while acknowledging unique barriers resulting from MTP use, such as high nicotine dependence.